2016
DOI: 10.1111/all.12895
|View full text |Cite
|
Sign up to set email alerts
|

Component-resolved analysis of IgA, IgE, and IgG4 during egg OIT identifies markers associated with sustained unresponsiveness

Abstract: Background In a previously reported CoFAR study, 55 subjects with egg allergy underwent randomized, placebo-controlled egg oral immunotherapy (eOIT). Active treatment induced desensitization in most and sustained unresponsiveness (SU) in a smaller subset. We hypothesized that component-resolved analysis of IgE, IgG4, IgA, IgA1, and IgA2 may identify potential biomarkers of SU in OIT subjects. Methods Longitudinal samples for 51 egg-allergic subjects (37 active, 14 placebo) were available. Egg white- (EW),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 37 publications
5
73
0
2
Order By: Relevance
“…3). These results were supported by the reports that Ara h 2-or eggspecific IgA and IgG in serum were increased at as early as 7 days or 3 months after starting the OIT [21,30]. In addition, the CDR3 sequences reported as Ara h 2-specific IgA and IgG were not observed in our analysis (Supplementary Tables 4-6) [21].…”
Section: Discussionsupporting
confidence: 91%
“…3). These results were supported by the reports that Ara h 2-or eggspecific IgA and IgG in serum were increased at as early as 7 days or 3 months after starting the OIT [21,30]. In addition, the CDR3 sequences reported as Ara h 2-specific IgA and IgG were not observed in our analysis (Supplementary Tables 4-6) [21].…”
Section: Discussionsupporting
confidence: 91%
“…Several authors have reported on serum biomarkers to predict clinical outcomes [13,14]. Allergen-specific IgG 4 is the most frequently used serum biomarker in studies of OIT because it could inhibit allergen IgE binding to B cells [15], and increased it when oral desensitization was induced [2][3][4][5][6][7][8]14].…”
Section: Discussionmentioning
confidence: 99%
“…Allergen-specific IgG 4 is the most frequently used serum biomarker in studies of OIT because it could inhibit allergen IgE binding to B cells [15], and increased it when oral desensitization was induced [2][3][4][5][6][7][8]14]. Wright et al [14] reported that the ratio of serum OM-specific IgG 4 /OM-specific IgE was significantly higher in the group that achieved sustained unresponsiveness whereas this was not the case for OVA. Our results are consistent with theirs.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of oral immunotherapy-treated patients become desensitized, which provides protection from reactions to unintentional ingestion of small amounts of food allergen. However, this initial desensitization is dependent upon regular intake of the dose [37•]. Allergic reactions are common, particularly during the build-up phase of oral immunotherapy, and this may be due to the higher dose than is used in other approaches outlined below.…”
Section: Potential Food Allergy Treatmentsmentioning
confidence: 99%